LANDSLIDE HAZARD ASSESMENT ON JAVA ISLAND Case Study: Landslides In Warungkiara, Bogor, Majalengka, Banjarnegara And Jember - Edi Prasetyo Utomo (Pusat Survei Geologi, 2013)
All of landslides recorded in Indonesia between 2003 – 2006, 90% of the events occurred on Java Island, Indonesia. Due to lack of long term statistical data, their characteristics are not well known. Based on the analysis of climate, geology, topography and landslide statistical data, the landslide characteristics on Java Island can be ascertained. It can be concluded that the frequency of occurrences of landslides are highest in the southern part of the West Java Province, followed by the Central Java Province and the East Java Province.Landslides on Java island can be classified based on their triggering factors, which comprise: rainfall, morphology, earthquakes, lithology, and the occurrence of active faults. As far as types of landslides are concerned, rockslides and toppling are rather rare, while most landslides are of the sliding (translation, rotation, block failure), creeping and debris flow types. The materials involved in landslides comprise weathered volcanic breccia, sedimentary material mixed with clay, mudstone, sandstone, limestone, marl and pyroclastic (deposits of volcanic ash and tuffaceous sand) and loam.Landslide events significantly occur in the rainy season, especially from December to April. Dead and missing victims by landslides increase when annual rainfall is in excess of 2100 mm. In this paper, with reference to the above mentioned factors and conditions, type of landslide prone areas and countermeasures will be discussed.Keywords: Landslide hazard, Java Island, classification, statistical data analysis.